HERMENEUTIKA FUNDAMENTAL: Memahami Fenomenologi Sebagai Orientasi Hermeneutika - Ardi, Mulia (IAIN Tulungagung, 2017)
Phenomenology is a method designed by Edmund Husserl as a rigorous and apodictic philosophical method. Phenomenology in praxis is often regarded as a hermeneutical effort. This opinion at least comes from a number of philosophers who expressed his support to phenomenology as a hermeneutic.Some philosophers like Heidegger, Dilthey, and Ricoeur put phenomenology as a hermeneutic project. John D. Caputo even specifically positioned phenomenology as a proto hermeneutic or early hermeneutics. The views of the philosophers concerning phenomenology in various discourse certainly can not be separated from the fact that the reading of reality which does phenomenology through epoche procedure actually parse traces of hermeneutics.